Behavioral Response of Halyomorpha halys (Hemiptera: Pentatomidae) and Its Egg Parasitoid Trissolcus japonicus (Hymenoptera: Scelionidae) to Host Plant Odors - Akotsen-Mensah, Clement; Blaauw, Brett R.; Rivera, Monique J.; Rodriguez-Saona, Cesar; Nielsen, Anne L. (Frontiers in Ecology and Evolution, 2021)
Insects use a range of cues to help them interact with each other and their host plants. Among these cues, olfaction plays a major role in host selection. The present study investigated the behavioral response of the brown marmorated stink bug, Halyomorpha halys (Stål), and its egg parasitoid, Trissolcus japonicus (Ashmead), to host plant-related odors. We used H. halys nymphs since their response to host odors is relatively unknown. In a Y-tube, we first evaluated the behavioral response of H. halys nymphs to whole-fruit odors of apple (Malus domestica (Borkh.)) and peach (Prunus persica (L.) Batsch). Subsequently, we tested the behavioral response of H. halys and T. japonicus to 18 selected, previously-identified synthetic fruit volatiles. In the greenhouse, we further tested H. halys attraction to the most promising of these volatiles individually and as blends. In single choice tests, H. halys nymphs preferred odors from apple and peach over the control (no odor). In dual choice tests, H. halys did not show any preference between apple and peach odors. Among the 18 volatiles tested, H. halys nymphs were attracted to ethyl salicylate (ES), undecane (UN) and ethyl acetate (EA) compared to the control. In the greenhouse, H. halys nymphs were similarly attracted to blends of 1:1 ratio of ES and EA but not to single compounds. Also in the Y-tube, female T. japonicus preferred the arm that had ES, β-caryophyllene, and decanal and a blend of these three compounds at a 1:1:1 ratio. Trissolcus japonicus was more attracted to the control arm than to the arm containing tridecane or α-pinene. These results indicate the potential of developing H. halys and T. japonicus attractants or/and repellents based on host plant volatiles and suggest possible adaptive responses of this pest and its egg parasitoid to similar host plant odors.